Political Education and its impact on the Future of Democracy - Bajari, Abner Herry; Renyaan, Dorthea; Risal, Semuel; Larantika, A. A Ayu Dewi (Formosa Journal of Applied Sciences, 2024)
This research aims to explore the role of political education in shaping the future of democracy in the Land of Papua. Democracy in Papua, as part of the Unitary State of the Republic of Indonesia, faces unique challenges related to political history, cultural identity, and limited access to education. This research identifies the importance of political education as a tool to increase citizen participation, political awareness, and understanding of democratic rights. Through a qualitative approach with interviews, surveys, and literature analysis, this study analyzes the impact of political education on social and political change in Papua. The research results show that although there are structural and cultural obstacles that influence the implementation of political education in Papua, there is great potential to strengthen democracy if political education is maximized.